The Effect of Loan and Intellectual Capital on Profitability with Credit Risk as Moderating - Eria Latifalia Erzha; Made Sudarma; Aulia Fuad Rahman (Jurnal Economia, 2019)
Abstract: This study aims to examine and empirically prove the moderating effects of credit risk on the relationship between the loan and intellectual capital with profitability. The sample selection technique uses purposive sampling, and data analysis uses moderated regression analysis. The result shows that loan has a positive effect on profitability, intellectual capital has positive effect on profitability, and credit risk moderates the effect of loan and intellectual capital on profitability. Keywords: loan, intellectual capital, credit risk, bank profitability.Pengaruh Pinjaman dan Modal Intelektual Terhadap Profitabilitas dengan Risiko Kredit sebagai PemoderasiAbstrak: Penelitian ini bertujuan untuk menguji dan membuktikan secara empiris efek moderasi risiko kredit terhadap hubungan pinjaman (loan) dan intellectual capital dengan profitabilitas. Teknik pemilihan sampel menggunakan metode purposive sampling dan analisis data menggunakan moderated regression analysis. Hasil penelitian menunjukkan bahwa pinjaman berpengaruh positif terhadap profitabilitas, intellectual capital berpengaruh positif terhadap profitabilitas, dan risiko kredit memoderasi pengaruh pinjaman dan intellectual capital terhadap profitabilitas. Kata Kunci: pinjaman, loan, intellectual capital, risiko kredit, profitabilitas bank.